Immunotherapy for neurological diseases, present and future - Ricardo Constantino Ginestal-López (Elsevier, 2018)
Objective: The objective of this work is to summarize the immunological treatment of neurological diseases, describing the present situation and the challenges and opportunities the future will present. Method: After topographically classifying the autoimmune neurological pathologies, a bibliographic analysis is made to present the most relevant ones regarding the available immunotherapeutic options. Likewise, new neurological entities that will be future candidates for immunotherapy are discussed. Results: There is a large number of neurological diseases with an autoimmune basis, even though their pathophysiology is, sometimes, only partially understood. Only a few randomized controlled clinical trials support the evidence of the immunotherapies with which we treat some of these diseases. This situation is rapidly changing among entities like multiple sclerosis where level 1 of evidence clinical studies are today´s standard. Alzheimer´s disease and migraine are two of the most prevalent conditions that are being incorporated to the group of diseases candidates for immunotherapy. Conclusions: Taking into account the rapidly growing number of immunological therapies and of neurological diseases potentially receiving them, an adequate evaluation of the impact these treatments will have on social and healthcare system grounds is necessary to reach compromises and consensus among all the professionals involved in the management of these pathologies